Defective INPP5E distribution in NPHP1‐related Senior–Loken syndrome. Issue 1 (11th December 2020) - Ning, Ke; Song, Emilie; Sendayen, Brent E.; Prosseda, Philipp P.; Chang, Kun‐Che; Ghaffarieh, Alireza; Alvarado, Jorge A.; Wang, Biao; Haider, Kathryn M.; Berbari, Nicolas F.; Hu, Yang; Sun, Yang
Abstract: Background: Senior–Loken syndrome is a rare genetic disorder that presents with nephronophthisis and retinal degeneration, leading to end‐stage renal disease and progressive blindness. The most frequent cause of juvenile nephronophthisis is a mutation in the nephronophthisis type 1 (NPHP1) gene. NPHP1 encodes the protein nephrocystin‐1, which functions at the transition zone (TZ) of primary cilia. Methods: We report a 9‐year‐old Senior–Loken syndrome boy with NPHP1 deletion, who presents with bilateral vision decrease and cystic renal disease. Renal function deteriorated to require bilateral nephrectomy and renal transplant. We performed immunohistochemistry, H&E staining, and electron microscopy on the renal sample to determine the subcellular distribution of ciliary proteins in the absence of NPHP1. Results: Immunohistochemistry and electron microscopy of the resected kidney showed disorganized cystic structures with loss of cilia in renal tubules. Phosphoinositides have been recently recognized as critical components of the ciliary membrane and immunostaining of kidney sections for phosphoinositide 5‐phosphatase, INPP5E, showed loss of staining compared to healthy control. Ophthalmic examination showed decreased electroretinogram consistent with early retinal degeneration. Conclusion: The decreased expression of INPP5E specifically in the primary cilium, coupled with disorganized cilia morphology, suggests a novel role of NPHP1 that it is involved in regulating ciliary phosphoinositide composition in the ciliary membrane of renal tubular cells. Abstract : In this study, we report a 9‐year‐old Senior‐Loken syndrome patient with NPHP1 deletion. We found the decreased expression of INPP5E specifically in the primary cilium, coupled with disorganized cilia morphology, suggests a novel role of NPHP1 in regulating ciliary phosphoinositide composition in the ciliary membrane of renal tubular cells.